Amyotrophic lateral sclerosis - Miller, Robert G. (Robert Gordon), 1942- (Demos Medical Pub., 2005)
ALS is not a curable disease, but it is a treatable one. Treatments are now available that can make a major difference in prolonging life and enhancing the quality of life for people with the disease, and there are treatments for many of the symptoms of ALS that can help ease its burden. Multidisciplinary teams in specialized ALS centers are providing top quality care and comprehensive rehabilitation for persons with ALS. In spite of the progressive nature of this disease and its clear tendency to shorten life, the momentum of research in this disease is expanding dramatically and numerous clin.